An Evaluation of Navigational Ability Comparing Redirected Free Exploration with Distractors to Walking-in-Place and Joystick Locomotion Interfaces - Peck, Tabitha C; Fuchs, Henry; Whitton, Mary C (Proceedings. IEEE Virtual Reality Conference, 2011)
We report on a user study evaluating Redirected Free Exploration with Distractors (RFED), a large-scale, real-walking, locomotion interface, by comparing it to Walking-in-Place (WIP) and Joystick (JS), two common locomotion interfaces. The between-subjects study compared navigation ability in RFED, WIP, and JS interfaces in VEs that are more than two times the dimensions of the tracked space. The interfaces were evaluated based on navigation and wayfinding metrics and results suggest that participants using RFED were significantly better at navigating and wayfinding through virtual mazes than participants using walking-in-place and joystick interfaces. Participants traveled shorter distances, made fewer wrong turns, pointed to hidden targets more accurately and more quickly, and were able to place and label targets on maps more accurately. Moreover, RFED participants were able to more accurately estimate VE size.